ANALISIS TINGKAT KESEJAHTERAAN ANGGOTA CU SEMARONG CABANG BATU LAYANG - Harnito Harnito; Aminuyati Aminuyati; Okianna Okianna (Universitas Tanjungpura, 2019)
AbstractThe purpose of this study was to determine the level of well-being of members of the CU SEMARONG Credit Cooperative in Batu Layang branch. The method used in this study was descriptive qualitative with a sample of 79 respondents from 347 populations. Data explanatory techniques ware direct communication techniques, indirect communication and documentation. Based on the results of the analysis showing the level of welfare of members of the CU SEMARONG Credit Cooperative in Batu Layang branch based on each indicator 1). population with high criteria with an average of 2.59 (12.72%). 2). health is included in the medium criteria with an average of 2.48 (12.98%). 3). Education in the medium criteria with an average of 2.46 (12.87%). 4). employment at high criteria with an average of 2.63 (13.76%). 5). the level and pattern of consumption are in a moderate position with an average of 2.09 (10.96%). 6). housing and high category environment with an average of 2.71 (14.18%). 7). poverty in the medium category with an average of 2.16 (11.30%). 8). other social categories in the medium category with an average of 2.21 (11.38%). From these eight indicators, it can be concluded that in general the level of welfare of members of the CU SEMARONG Credit Cooperative in Batu Layang branch is classified as prosperous with moderate criteria. Keywords: Analysis, CU SEMARONG, Walfare.